(untitled) (Princeton, N.J., 1945)
Includes bases of International Politics; The European realm of the great powers; The Afro-Asian realm of rival Imperialisms, The American realm between Europe; foundations of peace and a new World order.
Keywords: Hợp tác quốc tế,World politics,International cooperation,Chính trị thế giới; 1945-1955,1945-1955